Conflict between syntactic roles and semantic functions of the pattern "X showed/demonstrated Y" in translations from English into Russian (on the material of AstraZeneca's press releases) - Kovalchuk, Aleksandr V.; Matyushin, Alexey A. (Vestnik Tomskogo gosudarstvennogo universiteta. Filologiya, 2025)
In English medical texts, particularly if they are about clinical trial results, the construction "X showed/demonstrated Y" is frequently used, where X is an inanimate subject in the semantic role of agent, and Y is an inanimate complement. Being translated into Russian, its formally close correspondence "X pokazal/prodemonstritoval Y" is frequently used. However, it often contradicts the Russian language norms. The research aims to verify and validate a semantic and stylistic status of the construction "X pokazal/prodemonstritoval Y" as a literal translation correspondence for "X showed/demonstrated Y", identify and group different ways of how the English construction can be translated by other, non-literal ways, compare their frequency, and give practical recommendations. Comparative, lexicalsemantic and semantic-stylistic analyses help this research to achieve its aims. The analyzed material comprises 16 bilingual AstraZeneca press releases published during the whole year of 2023. The research reveals that the non-literal translation of "X showed/demonstrated Y" is used in every second case (50 %). Based on statistics, grammar, and dictionaries, we offer practical recommendations as such: (1) If "X showed/demonstrated Y" has an information source as the subject and a fact reported in this source as the complement, its literal translation is acceptable, although other constructions of the Russian language spectrum can be used. (2) If "X showed/demonstrated Y" has a drug as the subject and a fact about this drug as the complement, it is important to distinguish what exactly is being said about the drug: its property or its use effect. If you imply its property, a literal translation can be acceptable (e.g. preparat pokazal svoyu effectivnost') but its stylistic context should be taken into account as this usage is colloquial. On the other hand, if you imply its effect, it is highly recommended avoiding literal translation as the Russian verb pokazat'/prodemonstrirovat' has no relevant reason-cause meaning. In this case, it is possible either (a) to place the subject in position of circumstance, complement or adjective and, if necessary, change the verb (e.g. instead of "preparat pokazal snizhenie zabolevaemosti", you can write "blagodarya preparatu snizilas zabolevaemost'", or "na fone terapii preparatom proizoshlo snizhenie zabolevaemosti", or "v gruppe patsientov, prinimavshih preparat, snizilas zabolevaemost"; or (b) to change the verb (e.g. instead of "preparat pokazal snizhenie zabolevaemosti", you can write "preparat obespechil snizhenie zabolevaemosti", or "preparat snizil zabolevaemost', or "preparat sposobstvoval snizheniyu zabolevaemosti").